Evaluating the use of JAK inhibitors in inflammatory connective tissue diseases in pediatric patients: an update. (4th March 2022) - Chuprin, Jane; McCormack, Lindsay; Richmond, Jillian M.; Rashighi, Mehdi
ABSTRACT: Introduction: Connective tissue diseases (CTDs) are a category of conditions that affect tissues that support and provide structure to the body. These diseases include rheumatoid arthritis, systemic lupus erythematosus, dermatomyositis, and sclerosing diseases. CTDs can be caused by dysregulation of inflammatory pathways, specifically an upregulation of interferons and JAK/STAT pathway activation. Areas covered: While CTDs have historically been treated with broadly immunosuppressant medications such as corticosteroids and disease-modifying antirheumatic drugs (DMARDS), newer and more targeted immunomodulating medications called Janus kinase inhibitors (JAKi) have emerged as potential treatments. Expert opinion: While most studies regarding JAKi for CTDs have focused on adult populations, pediatric patients with CTDs may also benefit from JAKi therapy. Moreover, the JAK/STAT inhibitor tofacitinib has been approved by the FDA for the treatment of active polyarticular course juvenile idiopathic arthritis. In this review, we have summarized what has been published on the use of JAKi for various pediatric CTDs.